Testing undergraduate medical students’ ability to correctly identify skin conditions in skin of color—A pre-post-study at a medical school in Germany - Finn Abeck; Ines Heinen; Isabel Heidrich; Julian Kött; Rachel Sommer; Christine Blome; Martin Härter; Matthias Augustin; Stefan W. Schneider; Inga Hansen-Abeck; Nina Booken (PLoS ONE, 2026)
Background and objectives Limited representation of diverse skin types in dermatology training hinders physicians’ ability to diagnose and treat patients with skin of color (SoC), thus contributing to health disparities. This study evaluated the effectiveness of a mandatory seminar in improving medical students’ ability to correctly identify skin conditions in SoC, as measured by objective tests. Methods The pre-post design study was conducted among fourth year medical students at the University of Hamburg (Germany) between October 2024 and February 2025. A multiple-choice test using clinical images of eight SoC skin conditions assessed visual diagnostic skills at the beginning and end of a seminar. Results The analysis included surveys from a total of 142 students (57.7% female, mean age: 25.2 years). The lowest pre-seminar identification rates were observed for melasma (26.8%) and keloids (40.1%). The overall identification rate improved significantly from 54.8% at the beginning of the seminar to 92.5% at the end of the seminar. The greatest increases in the proportion of correct diagnoses were found for melasma (+ 65.5%), keloids (+ 51.4%), and tinea (+ 47.9%). Furthermore, self-assessed knowledge on skin type classification scales and anatomical and physiological differences between light skin and SoC increased at the end of the seminar. Conclusion The seminar effectively improved students’ ability to correctly identify skin conditions in SoC. Integrating SoC-focused training into medical curricula can bridge knowledge lacunae and thus help reduce health disparities by equipping future physicians in providing equitable care.